PENGUATAN KOMPETENSI PENGUJIAN MUTU BETON MELALUI PELATIHAN REBOUND HAMMER TEST BAGI SISWA SMK: PENGUATAN KOMPETENSI PENGUJIAN MUTU BETON MELALUI PELATIHAN REBOUND HAMMER TEST BAGI SISWA SMK - Nor Puji Lestari; Rio Devilito; Fikri Praharseno; Lalu Yahya Surya Buana; Suparman; Sriwahyuningsih Sulaiman; Suwarto; Wahjoedi; Arief Subakti Ariyanto; Parhadi (Politeknik Negeri Semarang, 2026)
Competence in concrete quality testing is an essential skill for vocational high school graduates in the construction sector to meet the demands of the construction industry. However, limited laboratory facilities and practical experience often hinder students from mastering non-destructive testing methods, particularly the Rebound Hammer Test. This community service program aimed to improve the knowledge and practical skills of students from the Building Construction and Housing Engineering Program at SMK Negeri Pringsurat in conducting concrete quality assessment using the Rebound Hammer Test. The program was implemented through a sequence of activities, including needs assessment, classroom instruction, equipment demonstration, guided hands-on practice, and evaluation using pre-tests, post-tests, practical observations, and participant response questionnaires. The results demonstrated a significant improvement in students' understanding of concrete quality testing principles, testing procedures, and interpretation of test results, as reflected in higher post-training evaluation scores. Furthermore, participants were able to operate the testing equipment according to standard procedures and expressed highly positive responses toward the practice-based learning approach. The program also strengthened teachers' instructional capacity through the provision of a training module that can be integrated into future laboratory learning activities. Although the program was limited by training duration and the availability of testing equipment, the integrated approach combining theoretical instruction, demonstrations, and guided practice proved effective in enhancing participants' competencies. This training model has the potential to be replicated in other vocational schools to support the development of industry-oriented competencies in the construction sector.